Oops, Clifford! - Bridwell, Norman (New York: Scholastic, 1999)
Clifford the big red dog is so large that he gets into trouble even when he is trying to do good deeds.
In logo on cover: Clifford, the big red dog.
"Cartwheel books."
Keywords: Dogs -- Fiction